Assessment of mother and child protection card utility in a rural block of Odisha - Susmita Dora; Debjyoti Mohapatra; Manish Taywade; Binod Kumar Patro; Vikas Bhatia (Wolters Kluwer Medknow Publications, 2023)
Background: Mother and Child Protection card was introduced for accelerating reduction in maternal, neonatal, and infant mortality and child under-nutrition & meant to be used by both beneficiaries and health care providers. It is a folding pictorial tool designed to assist mothers' understanding and monitor individual progress of maternal and child health and also enable the large networks of ASHAs, AWWs, and ANMs to converge their efforts and utilize the critical contact opportunities more effectively. Objective: To assess the completeness of information in MCP card filled by the AWW, ANM, and Beneficiary. Material and Methods: Twelve villages in mendhasal block of Khurdha district were selected for this study by multistage stratified random sampling method. MCP cards of Pregnant women from the second trimester onwards and Mothers of children 0-2 years of age were assessed for completeness using a Checklist. Results: A total of 34 and 46 items were checked for completeness in the MCP cards of Antenatal and post-natal women. The median entries found to be complete in Antenatal and Post-natal women were 34 and 26. Recording information on demographic details and antenatal care details was high but there was poor maintenance of other records like post-natal care, immunization, and growth chart. It was also found that beneficiaries are not marking the circles in the tablets consumption part. Conclusion: The study reported a gap in the maintenance of records in the Mother & Child Protection Card. Training for both the health care providers and mothers is needed for adequate use of the MCP card.